Microbial extracellular enzyme activity affects performance in a full-scale modified activated sludge process - Hassard, Francis; Biddle, Jeremy; Harnett, Richard; Stephenson, Tom (Elsevier, 2018)
The rate-limiting step of wastewater treatment is the breakdown of polymers by extracellular enzyme activity (EEA). The efficacy of EEA on biomass from full scale conventional activated sludge (AS) and modified AS with bench scale and full scale rotating biofilm reactors (RBR) was compared. The maximum amino-peptidase EEA was 394 ± 34 μmolL−1 min−1 for the bench RBR which was 11.7 and 4.5 times greater than maximum α-glucosidase and phosphatase EEA in these reactors. At full scale the RBR gave ~4.6, 13.5 and 6.3 times the EEA for amino-peptidase, α-glucosidase and phosphatase (based on enzyme Vmax) compared to the highest EEA in conventional AS biomass. Controlled overloading of the bench RBRs revealed that EEA increased with OLR up to 190 g tCOD m−2d−1 and further increases in OLR reduced the EEA. Pretreatment of wastewater by EEA in the RBR was linked to better performance of the modified activated sludge process. Maintaining high EEA of biofilms is critical for the design of high OLR wastewater treatment systems.
Keywords: Biofilm; Microbial extracellular enzyme activity; Hybrid activated sludge; Hydrolytic activity; Performance